1999
DOI: 10.1159/000007645
|View full text |Cite
|
Sign up to set email alerts
|

Study of a Primary Gastrinoma in the Common Hepatic Duct – A Case Report

Abstract: Primary endocrine neoplasms of the biliary tract are exceedingly rare. We report on a 60-year-old man with diarrhea, vomiting and gastroesophageal reflux disease, with a primary gastrinoma of the common hepatic duct. The tumor was positive for a variety of immunohistochemical markers. Postoperatively the patient’s symptoms disappeared and in the follow-up the patient was symptom free. To our knowledge, this is the first case in the literature of a primary gastrinoma in the common hepatic duct. The fact that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
18
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 4 publications
1
18
0
Order By: Relevance
“…Surgical resection is the treatment of choice and is the only chance for cure with a reported respectability rate up to 86% in the literature, and eugastrinemia in up to 60% post-operatively, 40% at 5 years, and 34% at 10 years [24][25][26] . Norton et al recommend surgical exploration of all ZES patients with resectable and sporadic disease as it has been shown to increase overall disease-related survival [27] .…”
Section: Discussionmentioning
confidence: 99%
“…Surgical resection is the treatment of choice and is the only chance for cure with a reported respectability rate up to 86% in the literature, and eugastrinemia in up to 60% post-operatively, 40% at 5 years, and 34% at 10 years [24][25][26] . Norton et al recommend surgical exploration of all ZES patients with resectable and sporadic disease as it has been shown to increase overall disease-related survival [27] .…”
Section: Discussionmentioning
confidence: 99%
“…Since the common bile duct is not located within the gastrinoma triangle, this unexpected localization makes the diagnosis difficult. To our knowledge, only two sporadic gastrinoma cases originating from the common bile duct have been reported in the literature (5,20). Extraduodenal, extrapancreatic and extranodal gastrinomas have been shown in 5.6% of the patients with ZES who underwent surgery (5).…”
Section: Discussionmentioning
confidence: 99%
“…Locations of gastrinomas outside the pancreas include the stomach, intestine, or liver 25–28. In one of the tumor specimens, a large tumor in the liver was revealed.…”
Section: Discussionmentioning
confidence: 97%
“…It was a weakly functioning gastrinoma as the level of gastrin in the blood was normal and the signs of ZES appeared only when the mass of the tumor became substantial. The existence of primary liver gastrinomas could be explained by the results of the studies26–30 that lead to a hypothesis that the liver and pancreas originate from common stem cells that still exist in adults. Furthermore, the experiments on the transplantation of epithelial precursor cells from the pancreas into the liver have revealed that they transformed to hepatocytes 29.…”
Section: Discussionmentioning
confidence: 99%